Cultural history of the United Arab Emirates - ., Mofeed Al-Zaidi (Al-Adab Journal, 2015)
This article is a study of Culture and its impact in the Society. It is Important to Understand the Structure of Social powers and people and Economic Structure. This Research Consist of three Chapters, the First about Economic Situation in the Emirates of the Coast Oman, and Second Chapter deals with Social Structure, and third Chapter concerns with the Culture ,police,education,cultural Communities , media and press, the woman Culture work, Population culture,arts,and cultural movements.